IMPLEMENTASI PROGRAM TOTAL QUALITY SERVICE DALAM UPAYA MENINGKATKAN KEPUASAN TAMU DI HOLIDAY INN RESORT BATAM - Saman, Saefuloh; Gaffar, Vanessa (THE Journal : Tourism and Hospitality Essentials Journal, 2012)
Study was to obtain findings on the effects of total quality service program to the satisfaction of guests at the Holiday Inn Resort Batam. Total Quality Service (TQS), is a fusion of all the functions of the company into a holistic philosophy that builds upon the concept of quality, teamwork, focusing on the customer (customer focus), the involvement of the total (total involvement), as well as continuous improvement. The method used in this study is descriptive and verification, with explanatory survey methods. The sample size is a number of long stay guests 79 using systematic sampling method. While the analytical technique used is multiple regression. The research results showed that total quality service has a significant effect on guest satisfaction. The results of calculations obtained Fhitung = 20,389, while Ftabel of the standard error 0.05 is 2.30. This shows that the total quality service effects guests satisfaction. The value of determination coefficient of 0.499. it showed that 44.9% guest satisfaction is influenced by total quality service while the remaining 55.1% is for other factors that affect guest satisfaction.